Effect and Configuration of 'Six Systems' for Safe Act of Rescue of Coal Mine Underground - SUN Ji-ping (Gong-kuang zidonghua, 2010)
The paper studied effect of safety monitoring and control system of coal mine in monitoring and early warning of serious accident of gas and fire and accident investigation, and put forward configuration scheme of the system and identification method of direct cause of gas explosion accident based on the system. It studied effect of monitoring system of underground personnel location in containment of super personnel quota production and emergency rescue of accident, and put forward configuration scheme of the system. It proposed mine communication scheme which takes mine-used dispatching communication system and mine broadcast communication system as foundation and takes mine mobile communication system as supplement，and standpoint that prohibits using mine-used IP telephone communication system and mine mobile communication system to replace mine-used dispatching communication system. It proposed that personnel going into high-gas mine should carry isolated self-rescuer, and the isolated self-rescuer should use with compressed oxygen. It proposed equipment requirement of refuge chamber and standpoint that rate of performance and cost of refuge chamber is better than life-saving shelter. It introduced self-help system of pressure ventilation and rescue system of water supply too.